Prevalence and Factors Associated with Infected Trypanosoma evansi in Buffaloes of Eastern Thailand - Panja, Kamonporn; Sananmuang, Tanida; Jankong, Thanakrit; Pornsukarom, Suchawan (Journal of Mahanakorn Veterinary Medicine, 2019)
Trypanosoma evansi is a protozoa which causes Trypanosomiasis or surra. The protozoa result in livestock economic loss, especially, cows and buffaloes. Buffaloes are the importance reservoirs. The objective of this study was aimed to determine the prevalence and factors associated with Trypanosoma evansi (T.evansi) infection in buffalos of Eastern Thailand. The samples were collected from buffalo blood during July - December 2016. Samples was selected by simple random technique. There were 153 samples, 51 samples from Sa Kaeo province, 48 samples from Chachoengsao provinces and 54 samples from Chonburi province. The overall prevalence of T. evansi infection was 5.25 %. The highest prevalence was found in Chachoengsao province (16.67%) while the disease was not found in Sa Kaeo and Chonburi province. Experimental results found that the area was significantly related to T. evansi infection (p<0.05). However, the other factors; number of buffaloes, age and gender, were not related to the T. evansi infection. Analysis of factors, which affected to be Trypanosomiasis in buffaloes of Eastern Thailand. Consist of two factors, the first factor is vaccination. The study results indicated that vaccination six months before sampling increased possibility of T. evansi infection more than unvaccinated. The second factor is insect vector. The farms with insect vector had more chance in T. evansi infection than those without insect vector. In Chachoengsao province, the additional factor to increase T. evansi infection was raising buffaloes with other animals.